Educational inclusion in the context of teacher training in Chile - Cornejo Espejo, Juan (2022)
Introduction: The article aims to unveil the way in which the CRUCH (Council of Rectors of Chilean Universities) universities are training their future teachers in the field of educational inclusion, for which the training itineraries and graduation profiles of the different pedagogies taught by these study houses present in its institutional web pages. From the methodological point of view, the research ascribes to a qualitative approach with a multiple-case design, taking into account the multiplicity of analysis units made up of the different study houses. For the production of information, the analysis of documents from the Internet was used, which in turn were analyzed through content analysis. Among the main findings, it stands out that, although most of the universities under study incorporated subjects related to inclusion, they are mainly focused on the attention of SEN (Special educational Needs), thus restricting the possibilities of understanding the inclusion processes and making other possible beneficiaries invisible; without counting on the perpetuation of the medicalizing paradigm that still underlies the training processes that is reinforced by current national legislation.